Construct and criterion validity of the Malaysia version of Lower Extremity Functional Scale (LEFS) - Muhammad Ariff Mohd Yunus; Ramli Musa; Mohd Yusof Nazri (Elsevier, 2017)
Objective: The objective of this study is to translate the Lower Extremity Functional Scale (LEFS) into the Malay language and to validate the resulting version. Methods: A two-stage observational study was conducted. The LEFS was initially cross-culturally adapted to Malay language through double forward and backward translation. The finalized version of Malay LEFS (M-LEFS) was subsequently validated for both construct validity and criterion validity. Participants (n = 208) with normal lower limb condition and various lower limb conditions completed the M-LEFS. Results: Reliability of M-LEFS revealed excellent Cronbach's alpha value of 0.98. Construct validity, evaluated using exploratory factor analysis, exhibited good factor loadings (>0.6) of all 20 items. Interestingly, we extracted 2 components which was not reported elsewhere. With a cut-off point of 60, the sensitivity of the scale was 99% and the specificity was 81%. Conclusions: The M-LEFS had very good psychometric properties among the studied population. Further studies are needed to enhance these preliminary outcomes in Malaysia.